Assessing Sources and Distribution of Heavy Metals in Environmental Media of the Tibetan Plateau: A Critical Review - Wang, Wenjuan; Ji, Xiaowen; Abakumov, Evgeny; Polyakov, Vyacheslav; Li, Gensheng; Wang, Dong (Frontiers in Environmental Science, 2022)
With a unique multi-sphere environmental system, the Tibetan Plateau (TP) plays an essential role in the ecological sheltering function for China and other parts of Asia. However, black carbon, persistent organic pollutants, and heavy metals (HMs) have been increased dramatically since the 1950s, reflecting rising emissions in Asia. In this context, the sources and distribution of HMs were summarized in the environment media of the TP. The results showed that (1) HMs in the TP may be generated from geogenic/pedogenic associations (Cu, Cr, Ni, As and Co) and anthropogenic activities of local or long-distance atmospheric transmission (Cd, Pb, Zn and Hg). (2) The atmospheric transport emission sources of HMs are mainly from the surrounding heavily-polluted regions by the Indian and East Asian monsoons and the southern branch of westerly winds. (3) Soil, water, snow, glacier, sediment, and vegetation act as vital sinks of atmospheric deposits of HMs; (4) Significant bioaccumulation of arsenic (As), lead (Pb), and methylmercury (MeHg) have been found in terrestrial and aquatic biota chains in the TP; (5) The enhancement of anthropogenic activities, climate change, glacial retreat and permafrost degradation had potential impacts on the behaviors and fates of HMs in the TP. Therefore, the ecological risk of HMs is of particular concern, and feasible and effective environmental safety strategies will be focused on reducing the adverse effects of inorganic pollutants in the TP. Our review will provide a reference for researchers to further study regional HMs pollution around the TP.